Effects of social skills training on some adaptive-compensatory parameters in patients with paranoid schizophrenia - V. Yu. Kudryashova; N. B. Lutova; A. Ya. Wuks (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
This paper examines the psychological aspects of adaptive-compensatory psychological mechanisms in patients with paranoid schizophrenia before and after social skills training. The features of self-regulation of behavior, the level of subjective control, life orientations and subjective perception of psychological characteristics of time are studied. The effects of social skills training were compared with a control group of patients who received only isolated drug therapy with psychotropic drugs. Positive dynamics was noted in both studied samples.The patients who took part in the study improved their ability to control impulses, increased behavioral flexibility, awareness of their contribution to the current situation and rational acceptance of responsibility for what is happening. Life goals also took shape better, the sense of manageability of life and satisfaction with it increased. The present has become perceived by patients with paranoid schizophrenia as more structured, saturated and predictable, and the past as realistic and tangible, which has a positive effect, including on the emotional background of patients. The effects of the training were clearly manifested when compared with a group of patients receiving only drug therapy. With combined treatment (social skills training and psychopharmacotherapy), patients begin to perceive the past more realistically, assess their actions and activity level more soberly, integration, awareness and structuring of past experience increases. This will allow patients with paranoid schizophrenia to facilitate the planning of their behavior in the future, as well as to increase the adequacy of the formation of cause-and-effect relationships and perception of what is happening, which has a beneficial effect on the ability to adapt to life in society and compensate for existing violations.